Adoption and Diffusion of Open Educational Resources (OER) in Education: A Meta-Analysis of 25 OER-Projects - Otto, Daniel (International Review of Research in Open and Distributed Learning, 2019)
The concept of open educational resources (OER) is becoming increasingly prominent in education. However, research circles around defining OER, content and forms of OER, technological features of OER, and the importance of the issue or lack thereof. Vital aspects such as the notion of the adoption of OER by educational practitioners remain underdeveloped. In order to shed light on the question of how to adopt OER in education, the article presents findings of a meta-study which critically reviewed 25 state-funded OER projects located in Germany. All projects aimed to anchor OER across educational areas, such as school, higher, continuing, and vocational education. The meta-analysis disclosed a mixed bag of results. Although interest and willingness to deal with OER can be confirmed, reservation is rooted in the complexity of the topic and especially the legal concerns. However, the findings demonstrate that OER can by no means be ignored in the context of teaching and learning in a digital world. Integrating OER as an aspect of existing educational training should, therefore, be encouraged. Concerning future design recommendations, to conflate OER with other pressing issues and to simultaneously emphasise its added value explicitly is a promising approach. Moreover, establishing central contact points in educational institutions to accompany and monitor actors on their path to OER appears to be necessary. Notwithstanding the concrete measures, any strategy must operate persistently at both levels, institutional and practical, embracing all relevant stakeholders.